Indological studies : prof. D. C. Sircar commemoration volume - Maity, S. K.; Thakur, Upendra (Delhi : Abhinav, 1987)
Festschrift honoring S.P. (Swadesh Prasad) Singhal, 1946-1986, Indian publisher.
Includes bibliographical references and index.
Keywords: India -- Civilization